Digital Intervention for Adolescents with Depression: A Scoping Review - Nunung Wahdania; Sri Padma Sari; Megah Andriany (GLOBAL HEALTH SCIENCE GROUP, 2025)
A significant public health problem is depression in adolescents. Depression is a mental disorder characterized by negative emotions and feelings of worthlessness. With the advancement of technology, interventions for adolescents experiencing depression can be delivered digitally through websites, apps, and other online platforms. Objective to review digital interventions used to address depression in adolescentsT. his article uses five data bases, namely ProQuest, Scopus, Scient Direct, EBSCOhost and PubMed . Article search from 21,554 articles which were then extracted to get 8 articles, peer review, full text and the last 5 years (2020-2025). Of the eight interventions analyzed, five were digital CBT-based interventions, two were psychoeducation and social support-based interventions, and one was a remote support therapy-based intervention. Apps enable a more cost-effective, more accessible, and more flexible approach compared to conventional methods. Digital interventions based on CBT, psychoeducation, and distance psychotherapy are the main approaches in treating adolescent depression.